Perception and intention to practice breastfeeding in adolescents in northeastern Mexico - Castro Sánchez, Ana Elisa; Ávila Ortiz., María Natividad; Zambrano Moreno, Adriana; Núñez Rocha, Georgina Mayela (Horizonte Sanitario, 2022)
Objective: To analyze the perception and intention to practice breastfeeding (BF) in adolescents of both genders who have not yet been parents. Material and Methods: This was a qualitative study based on grounded theory with empirical saturation. Twenty-one semi-structured interviews were conducted with students between 15 and 18 years of age in preparatory schools in Monterrey, Nuevo León, Mexico. Results: Four patterns on the perception and intention of practicing breastfeeding were identified: traditional; undecided; rejection; and egalitarian. Conclusions: The intention to support or practice BF is related to gender identities and the project of having children and / or a personallabor development project. There is convergence between different perceptions and intentions to practice BF in the future, which aims to review policies in this area. Keywords: Breastfeeding, adolescents, qualitative research, grounded theory.